2006
DOI: 10.1080/07294360600610370
|View full text |Cite
|
Sign up to set email alerts
|

The impact of institutional factors on student academic results: implications for ‘quality’ in universities

Abstract: This article situates the topic of student assessment and the moderation of assessment within a broader context of policy debates about the quality of teaching and learning in universities. The focus and discussion grew out of a research project which aimed initially to investigate factors related to academic success and failure in a Faculty of Arts. The study identified a range of student demographic and biographical factors significantly related to academic success and failure. However, there was also eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Amongst such concerns might be consistency of academic standards and assessment practices across and between higher education providers, quality of teaching and the quality of provision for learning, value for rand in terms of the cost to individuals and families of participation in higher education, and the reputation of academic courses and programmes in the eyes of employers (and hence the potential employability of graduates) (Wimshurst et al 2006). Academic predictors from the secondary level can be used but there are various other factors that influence the correlation between previous academic performance and university academic performance (McKenzie and Schweitzer 2001).…”
Section: Marnewickmentioning
confidence: 99%
“…Amongst such concerns might be consistency of academic standards and assessment practices across and between higher education providers, quality of teaching and the quality of provision for learning, value for rand in terms of the cost to individuals and families of participation in higher education, and the reputation of academic courses and programmes in the eyes of employers (and hence the potential employability of graduates) (Wimshurst et al 2006). Academic predictors from the secondary level can be used but there are various other factors that influence the correlation between previous academic performance and university academic performance (McKenzie and Schweitzer 2001).…”
Section: Marnewickmentioning
confidence: 99%
“…They have also mentioned that mentoring and engagement could be used to enhance the outcome/performance of the students or employees. Similarly, Wimshurst et al (2006), Zachariah (2007), and Allam and Ahmad (2013) stated in their investigations that quality can be measured through the mechanism of outcome and assessment to get to know the strengths and weaknesses of their institution where the practices are applied in the form of assessment.…”
Section: Factor 5 (Outcome and Assessment)mentioning
confidence: 99%
“…In the study of Kang, Kim, and Shin (2014), the difficulties faced by many international students were that they did not receive important notifications such as course registration and dormitory arrangement from the administration office. Wimshurst, Bates, and Wortley (2006) reported that it is helpful for the international students that the school communicate better with students about the evaluation methods or the administrative procedures of the university.…”
Section: Academic Factorsmentioning
confidence: 99%
“…Ren and Hagedorn (2012) suggested some innate characteristics of international students as significant factors; in particular, the region of origin were significantly related to international graduate students" GPA at the master"s level as well as gender and age. Wimshurst, Bates, and Wortley (2006) stated that gender affects the academic performance; female students gain better grades than male students. Jochems, Snippe, Smid, and Verweij (1996) argued that the academic success depends entirely on the student"s ability and effort.…”
Section: Other Factorsmentioning
confidence: 99%